Iterative method for determining boundaries and lidar ratio of permeable layer of a space lidar. (October 2018) - Mao, Feiyue; Pan, Zengxin; Wang, Wei; Li, Siwei; Gong, Wei
Highlights: The iterative method is more robust than the slope method and can obtain a reasonable layer base of a permeable layer under low SNR. The iterative method can obtain a reasonable lidar ratio of a permeable layer, which is a key parameter for retrieving the layer optical properties. The iterative method can also obtain the optimized layer top height of the next layer of a permeable layer in the iterative process of the current layer base detection. Abstract: Space lidar is a unique tool for detecting the 3D properties of cloud and aerosol layers. Layer boundaries and lidar ratio are significant preconditions for retrieving the layer optical properties of a space lidar. The CALIPSO (Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observations) team adopts the threshold method to accurately detect a layer top. However, the layer base detection continues to rely on the slope method, which causes considerable uncertainty. Furthermore, a fixed lidar ratio is mainly used for retrieving optical properties of layers of the same layer type, which also contains large uncertainty. To reduce the above uncertainties, we propose an iterative method to determine layer base and lidar ratio of a permeable layer of a space lidar on the basis of lidar ratio and transmission relationship. The simulated and measured experimental results demonstrate that the proposed iterative method simultaneously retrieves layer boundaries and lidar ratio accurately. The proposed iterative method has the potential to become a significant part of data retrieval of a space lidar in the future.